2014
DOI: 10.1186/1880-5981-66-96
|View full text |Cite
|
Sign up to set email alerts
|

Seismic structure of subducted oceanic crust near the slow-earthquake source region in the southern Ryukyu arc

Abstract: Seismic tomography and receiver function analysis were carried out to investigate the relation between the slab structure in the southern Ryukyu arc region and the occurrence of slow-slip events that repeat biannually. For calculation of the receiver function, 212 teleseismic earthquakes with magnitudes larger than 6.0 were selected, and teleseismic waveforms were observed using two short-period seismometers and one broadband seismometer. Assuming that each later phase in a receiver function was a wave convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Slab anomaly recovery tests and slab checkerboard tests (see Methods and Supplementary Figs 7–10) show that the fading of the low- V P layer at depth is a feature required by the data, and not a consequence of diminished resolution beneath 60 km depth. Tomography images of the subducting slab crust are increasingly common3132 but rarely detailed in 3D. Our inversion provides one of the clearest tomographic images of the subducting slab crust and confirms evidence from other seismic observables, for example, waveguide behaviour333435, converted teleseismic phases36 and receiver functions243738, that on most subduction zones a low- V P crustal layer persists to considerable depth.…”
Section: Resultssupporting
confidence: 74%
“…Slab anomaly recovery tests and slab checkerboard tests (see Methods and Supplementary Figs 7–10) show that the fading of the low- V P layer at depth is a feature required by the data, and not a consequence of diminished resolution beneath 60 km depth. Tomography images of the subducting slab crust are increasingly common3132 but rarely detailed in 3D. Our inversion provides one of the clearest tomographic images of the subducting slab crust and confirms evidence from other seismic observables, for example, waveguide behaviour333435, converted teleseismic phases36 and receiver functions243738, that on most subduction zones a low- V P crustal layer persists to considerable depth.…”
Section: Resultssupporting
confidence: 74%
“…Our tomographic results revealed a similar region of high‐ V p / V s oceanic crust (>1.8) just beneath the most active SSE occurrence area. The less‐active eastern side of this SSE area, which was unresolved by Nakamura (), calculated low‐to‐moderate V p / V s (<1.75) (Figure ). Thus, we inferred that our V p / V s image of the oceanic crust reflects fluid pressure.…”
Section: Resultsmentioning
confidence: 83%
“…High pore pressure in the oceanic crust is often cited as the cause of SSEs along plate boundaries (Kodaira et al, ). From seismic tomography, Nakamura () showed that the largest SSE region beneath the Ishigaki and Iriomote Islands corresponds to the plate boundary just above the high‐ V p / V s oceanic crust (1.78–1.83), and they interpreted this high V p / V s anomaly to be a reflection of a high fluid pressure zone. Our tomographic results revealed a similar region of high‐ V p / V s oceanic crust (>1.8) just beneath the most active SSE occurrence area.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 8, we compare the various crustal models for the western Pacific. We collected seismic refraction survey data across trenches in Japan (43 points in Table 2) reported by Iwasaki et al (1989Iwasaki et al ( , 1990, Hetland and Wu (2001), Kodaira et al (2002), Takahashi et al (2004Takahashi et al ( , 2009, and Nakamura (2014). For this region, the Moho depths from CRUST2.0 and from refraction data seem to be generally consistent.…”
Section: Crustal Model Comparisonsmentioning
confidence: 95%